Financial Resource Management and Its Influence on Students Academic Performance in Public Secondary Schools In Langata Sub-County, Nairobi County-Kenya - Odide, Martin Okoth (International Journal of Scientific Research and Management (IJSRM), 2021)
The aim of the study was to examine the influence of financial resource management on the students’ academic performance in public secondary schools in Lang’ata sub-county, Nairobi County- Kenya. The study was premised on behavioural leadership theory propounded by Kurl Lewin in the 1930’s which emphasizes that people can learn to become leaders through training and observation. The following research questions were formulated to guide the study: What is the influence of budget management on students’ academic performance in public secondary schools in Lang’ata sub – county, Nairobi County? ; What is the influence of financial controls on the students’ academic performance in public secondary schools in Lang’ata sub – county, Nairobi County? ; What challenges do Principals of Public secondary schools face in the management of finances?; What strategies, with regard to financial resource management, are used by Principals of Public secondary schools in Lang’ata sub-county to improve academic performance? Descriptive research design was adopted for the study. The study was conducted in public secondary schools. The target population comprised five (5) public secondary schools. Purposive sampling technique was used to draw 5 principals, 5 bursars, 5 B.O.M representatives, 15 H.O.Ds, 30 teachers and 200 students’ representatives giving a total of 260 participants. Data was collected using questionnaires, interview schedules, and observation schedules. A pilot test was conducted on some staff to ensure the validity of the instruments. Data obtained through open-ended questionnaires was analysed using descriptive and inferential statistics. Ethical issues such as confidentiality, informed consent, privacy and anonymity were given paramount considerations.Therefore, the findings of the study revealed that financial resources management can truly affect student’s academic performance. Furthermore, the researcher found out that not all staffs are involved in budget making or financial plans of the schools. Additionally, the researcher found out that most students are suffering due to lack of finances by their parents and guardians. Finally, financial stability goes hand in hand with educational success. Truly all teachers and staff need full adequate finances in order to ensure that the school’s programs run smoothly and with ease for all. Also the researcher found out that most students studying in public schools have fees challenges, especially those in the slums like Kibera constituency – Lan’gata Sub County. The study recommends that all Bursars and Boards of Management Representatives should be appointed with their merit certificate to the specific spot of the work in order to avoid any corruption in the field of their duties within the school environment. Additionally, students, should be provided with adequate teaching/learning materials; the teachers, heads of departments, finance committee, top management and the principal should treat the students fully as learners, and they should not dismiss any student from the school due to lack of fees; they should also provide counselling/ social workers departments to check on the students welfare and their mental problems regularly.  Finally, the study recommended the following for further study; financial resource management and its influence on student’s academic performance in private secondary schools in Lang’ata sub-county, Nairobi county-Kenya: to find out whether there are similarities in the findings of the study between public secondary schools and private secondary schools.R